Analysis of the impact of policies intervention on electric vehicles adoption considering information transmission—based on consumer network model. (September 2020) - Li, Jingjing; Jiao, Jianling; Tang, Yunshu
Abstract: Electric vehicles (EVs), which can relieve the pressure of energy and environment and revitalize the automotive industry, are paid great attention by the government. Existing research on the dynamic adoption process of EVs from the perspective of consumers based on complex social networks is insufficient. Based on the consumer network with dual attributes, i.e., positive/negative attitude and whether or not to adopt, this paper explores the impact of economic and information policies on EVs adoption rate by establishing a decision-making model of EVs adoption for consumers considering the effects of friend attitudes and power consumption information. The results show that: (1) The joint implementation of economic policies has a prominent effect on the adoption rate of EVs that is least affected by the subsidy cut policy when charging at home. (2) Enhancing popular science propaganda promotes the EVs adoption rate by increasing the initial proportion of positive attitudes in the consumer network. However, the promotion effect will be weakened if it exceeds a certain threshold. (3) Encouraging social discussion by expanding the number of friends has two sides to the EVs adoption rate. Finally, policymakers should consider the impact of consumers with different risk preferences on EVs adoption. Highlights: A decision model of EVs adoption is established based on the consumer network. EVs adoption rate is least affected by subsidy cut policy when charging at home. Enhancing popular science propaganda promotes EVs adoption rate. Encouraging social discussion has two sides on EVs adoption rate. Policymakers should consider the impact of consumers with different risk preferences.